ANALISIS MANAJEMEN DALAM UPAYA ADAPTAS DAN MITIGASI PERUBAHAN IKLIM DI KELURAHAN MIROTO, KECAMATAN SEMARANG TENGAH, KOTA SEMARANG - Sekarini, Hayu; Sulandari, Susi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
The current problem of climate change has become an environmental issue because it has an big impact in society. Effort has been made by Indonesian government to resolve this climate change issue by applying Program Kampung Iklim (PROKLIM) which contains climate change adaptation and mitigation. Therefore, a management process is needed to manage those adaptation and mitigation effort. This research aimed to analyze management and the supporting and inhibiting factors of climate change adaptation and mitigation in Miroto Village Central Semarang Sub-district Semarang City. This study is a descriptive research with qualitative approach. This research was conducted in the Miroto Village with informants for the Kasie Pemulihan Lingkungan dan Perubahan Iklim Dinas Lingkungan Hidup dan Kebersihan Kota Semarang, Headman Miroto, Kasie Pemerintahan dan Pembangunan Kelurahan Miroto, Head of LPMK Miroto, and the society. The data was collected through interviews, observations, documentation and literature studies. Data analysis using data analysis techniques developed by Miles and Huberman. The result of this research showed that management of climate change adaptation and mitigation in Miroto village had not been optimal, because there were still many problem in planning, organizing and actuating aspects. In planning aspect, the comprehension of guidelines in Peraturan Gubernur Jawa Tengah Nomor 43 Tahun 2012 tentang Rencana Aksi Daerah Penurunan Emisi Gas Rumah Kaca tahun 2010-2020 were still very low, there were only a few the adaptation and mitigation activities of climate change, and there were not a spesific schedule for the activities. In organizing aspect, the special team that had been made did not function properly, and there were only a few cooperation. In actuating aspect, the social participation was still low. The recommendations is for planning by socialize the guidelines in Peraturan Gubernur Jawa Tengah Nomor 43 Tahun 2012 add more the adaptation and mitigation activities of climate change, and arrange a specific schedule; organizing by make an organizational structure in RT/RW, and adding more cooperation; actuating by holding routine voluntary work.